new species of Burksiella from Mexico (Hymenoptera: Trichogrammatidae) - Ávila-Rodríguez, Verónica; Myartseva, Svetlana N.; González-Hernández, Alejandro (Instituto de Ecología, A.C., 2011)
A new species of trichogrammatid, Burksiella mexicana sp. nov., is described based on specimens collected in Tamaulipas, Mexico, using morphological characters.